1998
DOI: 10.1126/science.282.5397.2230
|View full text |Cite
|
Sign up to set email alerts
|

A Free-Fall Determination of the Newtonian Constant of Gravity

Abstract: Recent determinations of the Newtonian constant of gravity have produced values that differ by nearly 40 times their individual error estimates (more than 0.5%). In an attempt to help resolve this situation, an experiment that uses the gravity field of a one-half metric ton source mass to perturb the trajectory of a free-falling mass and laser interferometry to track the falling object was performed. This experiment does not suspend the test mass from a support system. It is therefore free of many systematic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 10 publications
0
71
0
Order By: Relevance
“…[19,20] 38.9 -77.02 6.6726 ± 0.0005 6.6720 ± 0.0041 Boulder (JILA) [21] 40 -105. 27 6.6873 ± 0.0094 Gigerwald lake [22,23] 46.917 9.4 6.669 ± 0.005 (at 112 m) 6.678 ± 0.007 (at 88 m) 6.6700 ± 0.0054 Zurich [24,25] 47.4 8.53 6.6754 ± 0.0005 ± 0.0015 6.6749 ± 0.0014 Budapest [26] 47.5 19.07 6.670 ± 0.008 Seattle [14] 47.63 -122.…”
Section: Comparison With Laboratory Measurementsmentioning
confidence: 99%
“…[19,20] 38.9 -77.02 6.6726 ± 0.0005 6.6720 ± 0.0041 Boulder (JILA) [21] 40 -105. 27 6.6873 ± 0.0094 Gigerwald lake [22,23] 46.917 9.4 6.669 ± 0.005 (at 112 m) 6.678 ± 0.007 (at 88 m) 6.6700 ± 0.0054 Zurich [24,25] 47.4 8.53 6.6754 ± 0.0005 ± 0.0015 6.6749 ± 0.0014 Budapest [26] 47.5 19.07 6.670 ± 0.008 Seattle [14] 47.63 -122.…”
Section: Comparison With Laboratory Measurementsmentioning
confidence: 99%
“…In a cold atom gravimeter version of the G-measurement the relative standard uncertainty-mainly from positioning errors-was of about 4.6 × 10 −4 9 for a total source mass of about 500 kg of tungsten. Schwarz et al reported a relative standard uncertainty of 160 × 10 −6 due to positioning errors and source mass density variations 7 . In a beam balance experiment at the University of Zurich two cylindrical vessels, filled with 14 metric tons of mercury were used 3 .…”
Section: Source Mass Density Inhomogeneities and Positioning Errorsmentioning
confidence: 99%
“…Our plan is to use numerous small metal spheres instead of big cylinders as done by Schwarz et al 7 or Lamporesi et al 9 Let us make some basic considerations in order to compare solid cylinder source masses with approximately the some volume filled with spheres. Assume twelve identical solid cylinders with a height of h = 15 cm and radius of 5 cm.…”
Section: Source Mass Density Inhomogeneities and Positioning Errorsmentioning
confidence: 99%
See 2 more Smart Citations